A University-Community Problem Based Mobile Health Unit Solution: Indirect and Direct Measures of the Impact of Rural Health in the (International Journal of Studies in Nursing, 2018)
The development of a medical home is an integral component in decreasing health disparities among disenfranchised communities. Mobile health clinics contribute to increasing access to health services, promoting health education, and improving care coordination especially among low income rural patients. This problem based solution, case study describes the experience of a University-community based partnership in the development of a mobile clinic model within ambulatory Community Medical Health. In 2014, a university based, nursing program initiated, mobile health unit was created to offer basic medical care to rural health areas in the Central Valley. The following case describes how this was accomplished, what outcomes were tracked and what lessons were gleamed as a means of improving the process for future endeavors or as a model to others looking to develop a similar project. Over the past two years the mobile health unit has shown the increased need for medical services as evident by an increase of patient visits in these areas. In addition, implementation results and considerations are discussed including key process indicators, limitations and future model directions.